Odpowiedzi

2010-03-30T21:47:58+02:00
A) (2x-1):5-(x-2):2=0,7x /10
2(2x-1) -5(x-2)=7
4x-2-5x+10=7
4x-5x=7-10+2
-x=-1 / (-1)
x=1

b) 2x-(3x+5):4=-1/4x-1 /4
8x-(3x+5)=-x-1
8x -3x-5=-x-1
8x-3x +x=-1+5
6x=4//6
x=1/6
11 3 11
  • Użytkownik Zadane
2010-03-30T21:50:30+02:00
(2x-1):5-(x-2):2=0,7x /*10
2(2x-1)-5(x-2)=7x
4x-2-5x+10=7x
4x-5x-7x=2-10
-8x=-8
x=1

2x-(3x+5):4=-1\4x-1 /*4
8x-3x-5=-x-4
8x-3x+x=-4+5
6x=1
x=1/6
5 4 5
2010-03-30T21:50:33+02:00
(2x-1):5-(x-2):2=0,7x/*10
4x-2-5x+10=7x
8x=8
x=1


3 2 3